Respuesta :

Answer:

[tex]a = \frac{ - 6}{5} b + \frac{18}{5} [/tex]

[tex]b = \frac{ - 5}{6} a + 3[/tex]

Step-by-step explanation:

Let's solve for a .

[tex]5a+6b=18[/tex]

Step 1: Add -6b to both sides.

[tex]5a+6b+−6b=18+−6b[/tex]

[tex]5a=−6b+18[/tex]

Step 2: Divide both sides by 5.

[tex] \frac{5a}{5} = \frac{ - 6b + 18}{5} [/tex]

[tex]a = \frac{ - 6}{5} b + \frac{18}{5} [/tex]

Let's solve for b.

[tex]5a+6b=18[/tex]

Step 1: Add -5a to both sides.

[tex]5a+6b+−5a=18+−5a[/tex]

[tex]6b=−5a+18[/tex]

Step 2: Divide both sides by 6.

[tex] \frac{6b}{6} = \frac{ - 5a + 18}{6} [/tex]

[tex]b = \frac{ - 5}{6} a + 3[/tex]

Hope it is helpful....

Ver imagen Аноним